Sponsored ads in instagram as a marketplace and the concept of social affiliation - (:unkn) unknown (Peter Lang Publishing Group, 2019)
As the Internet became widespread since the beginning of the 90s, different communication programs such as mIRC and ICQ developed, which enabled interpersonal and group interaction. In this period, privacy was a priority for people. Commonly most of the users were picking up a nickname, instead of using their real names as it perceived as a potential risk to personal information. After nearly a decade, the concept of social media emerged and became very popular in a short time due to its multimedia sharing feature. It was a new form of communication and a way of informing the first-degree connections about personal facts. With the change of Internet usage habits, people started to share their daily life intensely via their social media by creating accounts on different social media platforms with their real names. These social media accounts built around user identities (Kietzmann, Hermkens, McCarthy and Silvestre, 2011, p. 243). There were no direct commercial activity or sales actions in this early period of internet communication, except product advertisements on search engines with very simple banner ads. The first internet advertising campaign had started within a website “hotwired.com” and expanded via search engines (Cho, 2001, p. 45-56). This very first advertisement was a display ad which was called banner. Main expectation from this internet ad was contributing to brand awareness, just like today. With the increase in the number of search engines, the number of ads on the internet proliferated. At the beginning…. © Peter Lang GmbH.